2012
DOI: 10.1089/cap.2011.0114
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Informant Agreement on the Anxiety Disorders Interview Schedule in Youth with Autism Spectrum Disorders

Abstract: These data suggest that parent and youth agreement regarding the presence of clinical levels of anxiety is markedly poor among youth with ASD. Additionally, clinicians are likely to base their diagnostic impressions on parent report, placing minimal emphasis on child report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 33 publications
9
55
0
Order By: Relevance
“…A previous meta-analysis of CBT trials for anxiety in typically developing youth found that youth often reported lower treatment effect sizes than their parents' reports [54]. These results are concordant with previous studies that have reported poor parent/clinician and child diagnostic agreement on anxiety measures in typically developing youth (e.g., ADIS; [55]) and youth with ASD (e.g., ADIS; [31]). It may be that children with ASD have difficulty reporting on their symptoms due to limited insight into symptoms and/or treatment effects, difficulty reporting on internal states, and secondary to the effects of comorbidity (e.g., inattentive youth may have difficulty participating in evaluations).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A previous meta-analysis of CBT trials for anxiety in typically developing youth found that youth often reported lower treatment effect sizes than their parents' reports [54]. These results are concordant with previous studies that have reported poor parent/clinician and child diagnostic agreement on anxiety measures in typically developing youth (e.g., ADIS; [55]) and youth with ASD (e.g., ADIS; [31]). It may be that children with ASD have difficulty reporting on their symptoms due to limited insight into symptoms and/or treatment effects, difficulty reporting on internal states, and secondary to the effects of comorbidity (e.g., inattentive youth may have difficulty participating in evaluations).…”
Section: Discussionsupporting
confidence: 85%
“…In particular, the child's report, when compared to the reports of the parent and clinician, is frequently discrepant [18,27,31]. This disparity may be the result of the child's limited insight into his/her anxiety symptoms (e.g., lack of recognition that anxiety symptoms are clinically significant and/or are impairing) or comorbid conditions (e.g., attention difficulties, oppositional behaviors) [2,5,6,15].…”
Section: Anxiety Informantmentioning
confidence: 99%
“…Second, internal consistency for the PARS and SRPs were relatively low, which could impact the conclusions. Although psychometrically sound, the PARS has demonstrated fair internal consistency in typically developing youth and in those with ASD [38,40], which has been suggested to relate to the associated but not redundant item content. Third, use of an open trial prevented the incorporation of a control group with which to compare outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, severity of physical symptoms of anxiety was assessed using an item from the PARS as rated by the parent, youth, and clinician. The PARS has acceptable reliability and validity [39] and has been shown to be acceptable for use among youth with ASD [40]. Internal consistency ratings for the PARS in the sample were .53 at baseline, and .80 at post-treatment.…”
Section: Pediatric Anxiety Rating Scale (Pars)mentioning
confidence: 90%
See 1 more Smart Citation